Quality assessment of comparative diagnostic accuracy studies: our experience using a modified version of the QUADAS‐2 tool. (10th June 2013) - Wade, Ros; Corbett, Mark; Eastwood, Alison
<x xml:space="preserve">Abstract</x> Assessing the quality of included studies is a vital step in undertaking a systematic review. The recently revised Quality Assessment of Diagnostic Accuracy Studies (QUADAS) tool (QUADAS‐2), which is the only validated quality assessment tool for diagnostic accuracy studies, does not include specific criteria for assessing comparative studies. As part of an assessment that included comparative diagnostic accuracy studies, we used a modified version of QUADAS‐2 to assess study quality. We modified QUADAS‐2 by duplicating questions relating to the index test, to assess the relevant potential sources of bias for both the index test and comparator test. We also added review‐specific questions. We have presented our modified version of QUADAS‐2 and outlined some key issues for consideration when assessing the quality of comparative diagnostic accuracy studies, to help guide other systematic reviewers conducting comparative diagnostic reviews. Until QUADAS is updated to incorporate assessment of comparative studies, QUADAS‐2 can be used, although modification and careful thought is required. It is important to reflect upon whether aspects of study design and methodology favour one of the tests over another. © 2013 Crown copyright.